Des lieux avec lesquels penser, des livres auxquels penser - Anders Burman (IdeAs)
Many Aymara men and women claim that human knowledge as transmitted through language is pure ‘siwsawi’, i.e. talk, opinions, views and judgments of particular individuals. As such it is knowledge of a particular kind; it is knowledge concerning the opinions of other humans, nothing else. It is thereby significantly different from the non-linguistic, experiential knowledge that is lived-through and gained in, from, with and within the world. This kind of knowledge is ‘ukamaw’, the way things are. Lines of reasoning such as these have been addressed by linguists interested in the dynamics of ‘evidentiality’, i.e. the way languages provide an array of mechanisms for communicating how people regard the source and trustworthiness of their knowledge. It has been shown that Aymara speakers constantly use linguistic ‘data-source marking’ in order to indicate whether they are speaking from personal experiential knowledge, from knowledge acquired through language, or from non-personal knowledge. In this paper, the two first categories will be discussed in some detail. When people distinguish between the ‘siwsawi’ nature of the knowledge acquired through human language and the ‘ukamaw’ nature of the personal knowledge acquired through non-linguistic interaction with other knowledgeable subjects in the world, they use a fundamental Aymara linguistic logic. In Aymara society, the failure to indicate from what kind of knowledge one speaks is looked upon with suspicion. When university lecturers fail to do so, e.g. when they seem to claim to have personal knowledge of a certain topic for having read a book about it, Aymara students tend to come to the conclusion that lectures and books are good enough if you are interested in people’s opinions and judgments, but they are no more than siwsawi; words said, heard and read, not experience lived. Thus, this way of distinguishing between different kinds of knowledge according to their source and supposed reliability has interesting implications for the current process of decolonization of the Bolivian University and the recent establishment of ‘indigenous universities’ as integral parts of the decolonizing state politics launched by the Evo Morales administration. In this paper I pose the question that if books and lectures are basically about the opinions and judgments of particular individuals, and proper knowledge is to be gained only in the experiential, non-linguistic, inter-relational dealings with and in the world, wouldn’t a project aimed at decolonizing knowledge and decolonizing the University precisely by way of books and lectures, i.e. a logocentric project of decolonization, be a venture fated to reproduce the colonial epistemological asymmetries of knowledge production? On the one hand, then, this paper scrutinizes the problems linked to the ‘siwsawi’ nature of conventional (colonial) academic knowledge in relation to a critical process of decolonization. On the other hand, it explores the ‘ukamaw’ nature of experiential knowledge and the prospects for this kind of knowledge to lay the fundaments for a decolonial epistemological transformation of the Bolivian University. Fundamentally, this paper addresses issues such as what it means to know, what knowledge is, and what it means to be a knowing and knowledgeable subject in the Bolivian Andes today, in a context where subalternized traditions of thought gain new urgency in new educational and political dynamics and where different visions and claims of truth coexist, coalesce and collide.